Satisfaction with Life Scale (SLS-6): First validation study in Parkinson's disease population. (April 2016) - Ambrosio, Leire; Portillo, Mari Carmen; Rodriguez-Blazquez, Carmen; Martínez-Castrillo, Juan Carlos; Rodriguez-Violante, Mayela; Serrano-Dueñas, Marcos; Campos-Arillo, Víctor; Garretto, Nelida Susana; Arakaki, Tomoko; Álvarez, Mario; Pedroso-Ibáñez, Ivonne; Carvajal, Ana; et al.
Abstract: Introduction: To explore the psychometric attributes of a new Satisfaction with Life Scale (SLS-6) in a wide Spanish-speaking population with Parkinson's disease (PD). Methods: This was an international, cross-sectional study. Several rater-based and patient-reported outcomes measures for evaluation of PD (e.g., Scales for Outcomes in Parkinson's Disease-Motor) and other constructs (e.g., Duke-UNC Functional Social Support Questionnaire, Scale for Living with Chronic Illness) were applied together with the SLS-6. Acceptability, scaling assumptions, reliability, precision, and construct validity were tested. Results: The study included 324 patients from five countries, with age (mean ± standard deviation) 66.67 ± 10.68 years. None of the SLS-6 items had missing values and all acceptability parameters fulfilled the standard criteria. Scaling assumptions allowed the calculation of a summary index from items 2 to 6, complementary to the global evaluation (item 1). For these five items, Cronbach's alpha was 0.85; the corrected item–total correlation 0.53–0.73; inter-item correlation, 0.45–0.70, with an item homogeneity index of 0.55. The standard error of measurement, based on Cronbach's alpha for a single observation, was 3.48. SLS-6 correlations were moderate to strong (rs ≥ 0.35) with the patient-reported outcomes and weak to moderate with the rater-based assessments used in the study. The SLS-6 total score was significantly different according to PD severity levels established according to Hoehn and Yahr staging, Clinical Impression of Severity Index, and Patient-Based Global Impression of Severity scale. Conclusion: The results suggest that SLS-6 is an easy, feasible, acceptable, consistent, precise and valid measure to evaluate satisfaction with life in PD patients. Highlights: Satisfaction with life is the cognitive component of well-being. It is relevant for quality of life and satisfaction with care. A new scale (SLS-6) has been applied and tested in Parkinson's disease (PD). The SLS-6 showed satisfactory psychometric attributes in this study. The SLS-6 is usable for PD and proposed to cover satisfaction with treatment.